PRIMARY PRODUCTIVTY STUDIES IN SOME AQUATIC BODIES OF KOLLAM DISTRICT (KERALA) - SAHIB, S. SYNUDEEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Primary productivity of a water body gives a quantitative information about the amount of energy available to support bio-activity of the system. Three aquatic bodies namely Parappar reservoir, Sasthamcotta lake and Kallada river were selected to conduct primary productivity studies. The studies were carried out from November (19980 to April (1999).